Face off. (Economist, 2007)
The article discusses the plan by Google Inc. and several social networking web sites to make online social networks more open through a set of standards, called OpenSocial, that allow software developers to write applications to work with any participating network. In contrast, the web site Facebook allows developers to write applications, or widgets, specific to its site only.